2020
DOI: 10.21203/rs.3.rs-50686/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perfluoroalkyl substances are associated with elevated blood pressure and hypertension in highly exposed young adults

Abstract: BackgroundResidents in a large area of North-Eastern Italy were exposed to perfluoroalkyl substances (PFAS) via drinking water. Studies on the association between PFAS and blood pressure levels are limited, and results are inconsistent. Using cross-sectional data from the Regional health surveillance program, we aimed to quantify the associations between PFAS serum concentrations and blood pressure and hypertension prevalence.MethodsThe study comprised 16,224 individuals aged 20-39 years. Pregnant women (n=327… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
(67 reference statements)
0
3
2
Order By: Relevance
“…Fewer studies address PFAS and hypertension, which is a stronger risk factor for atherosclerotic disease. Recent cross-sectional work in NHANES-enrolled adolescents, and in a separate young adult prediabetics with substantial PFAS exposure, suggest a possible relationship of PFAS to this atherosclerotic risk factor as well 12,44,45 . Our results do not support a current addition of AAC to the list of associated risk factors.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Fewer studies address PFAS and hypertension, which is a stronger risk factor for atherosclerotic disease. Recent cross-sectional work in NHANES-enrolled adolescents, and in a separate young adult prediabetics with substantial PFAS exposure, suggest a possible relationship of PFAS to this atherosclerotic risk factor as well 12,44,45 . Our results do not support a current addition of AAC to the list of associated risk factors.…”
Section: Discussioncontrasting
confidence: 83%
“…Recent cross-sectional work in NHANES-enrolled adolescents, and in a separate young adult prediabetics with substantial PFAS exposure, suggest a possible relationship of PFAS to this atherosclerotic risk factor as well. 12,44,45 Our results do not support a current addition of AAC to the list of associated risk factors. The presence of a weak, non-significant association in a planned gender comparison opens the question of whether an association would be seen in a larger sample size.…”
Section: Discussioncontrasting
confidence: 82%
“…28 Similarly, in a cross-sectional study of 16 224 adults aged 20 to 39 years living in Italy who were exposed to PFAS-contaminated drinking water, PFOA was associated with higher SBP in men and DBP in women; however, significant associations of PFOA, PFOS, PFHxS, and perfluorononanoate with prevalent hypertension were observed only in men. 29 Other cross-sectional studies reported no associations of PFAS with prevalent hypertension and blood pressure, 30–32 whereas one cross-sectional study of 154 male anglers aged 50 years and older in Wisconsin 30 found an inverse association between perfluorononanoate and prevalent hypertension. All these studies considered similar sets of confounders, including demographic factors, socioeconomic status, and lifestyle factors in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Three cross-sectional studies reported significant positive associations of specific PFAS with prevalent hypertension and elevated blood pressure. 27–29 In a study of 2934 adults who participated in the 2003 to 2004 and 2005 to 2006 National Health and Nutrition Examination Survey, the adjusted odds for prevalent hypertension were 2 and a half-fold higher in those at the 80th versus the 20th percentiles of PFOA concentrations; no relationship was found for other PFAS. 27 A cross-sectional study of 1612 Chinese adults aged 22 to 96 years reported significant relationships of prevalent hypertension with PFOS, PFOA, perfluorononanoate, and perfluorobutanoate, with more pronounced effects observed in females; whereas no associations were detected for other compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation